Complete structure of the alpha B-crystallin gene: conservation of the exon-intron distribution in the two nonlinked alpha-crystallin genes. - Quax-Jeuken, Y (1985)
We isolated bovine complementary DNA clones for the alpha A- and alpha B-crystallin subunits. The alpha B cDNA clone was used to isolate an alpha B-crystallin gene. This gene, derived from hamster, occurs as a single copy in the genome and is 3.2 kilobases long. The coding sequences are spread on three exons with a total length of 709 nucleotides. The exon-intron distribution of the hamster alpha B-crystallin gene is similar to that of the alpha A-crystallin gene except for the 69 nucleotides that specify the 23 "insert" residues of the alpha AIns chain by means of differential splicing. The 3' noncoding region of the alpha B mRNA (140 bases), which is short compared with the alpha A mRNA (520 bases), shows a remarkable homology between calf and hamster. Both alpha-crystallin cDNA clones have been used to assign the chromosomal location of the corresponding human genes with the aid of somatic cell hybrids. It is shown that the single-copy alpha A- and alpha B-crystallin genes are located on different chromosomes.